ADMINISTRATIVE-TERRITORIAL REGULARITIES IN VARIABILITY FEATURES OF DERMATOGLYPHICS MEN IN UKRAINE WITH AN AVERAGE LEVEL INTENSITY OF CARIES - Шінкарук-Диковицька, М.М.; Klimas, L.A. (World of Medicine and Biology, 2015)
Aim of our work – to explore the features of dermatoglyphics in men with an average level of intensity infestation by caries depending on their place of residence in different administrative-territorial regions of Ukraine. Materials and methods On the base of Department of Pediatric Dentistry and Scientific Research Center Vinnitsa National Medical University named after Pirogov carried out a survey of more than 3,500 men aged from 19 to 35 years from different regions of Ukraine to establish somatically healthy persons with a special screening questionnaire. This resulted in selected 410 somatic healthy men in the third generation residents the respective regions of Ukraine: 72 - from the north, 47 - from the south, 165 - from the central, 71 - from the west, 45 residents of the eastern regions. All of them analyzed the medical and social factors conditions of life, indicators of using oral care products and subjective assessment of periodontal tissues, the results of which indicate a fairly high homogeneity of samples somatically healthy men from different regions of Ukraine. Selected men conducted a complete dental examination. The intensity of teeth caries lesions in permanent occlusion was determined by the index of the CFR. Assessing the level of caries performed on the basis of criteria of intensity caries of Global Bank WHO dental data for adults Assessing the level of caries performed on the basis of criteria of intensity caries of data dental Global Bank WHO for adults: 0.2 - 1.5 - very low; 1.6 - 6.2 - low; 6.3 - 12.7 - average; 12.8 - 16.2 - high; 16.3 and above - a very high indicator of dental caries intensity. Dermatoglyphic study performed by the method of H. Cummins and Ch. Midlo. Statistical analysis of the results conducted in the package «STATISTICA 6.1». Results. Discussions Established next specificity of dermatoglyphic picture in somatic healthy men with an average level of intensity of caries among different administrative-territorial regions of Ukraine: for residents of the central region supposes the availability of patterns with medium intensity formation of combs and patterns on hypothenar and thenar, and for the north - in the presence of competing pattern either with high or with zero intensity formation of combs; for residents of the central region consists in the predominance of patterns with high intensity formation of combs and rare pattern with low intensity formation of combs, and for the south - with zero and high intensity formation of combs; for residents of the central region consists in the predominance patterns with medium intensity formation of combs, for them inherent increased pattern of hypothenar, thenar and II interdigital interval of palm rest and for a western - with high and zero intensity formation of combs; for residents of the central region consists in the predominance of patterns with high intensity of formation of combs, for them inherent increased pattern of II interdigital interval palm of hand and for the east - with high and medium intensity formation of combs; for residents of the western region, consists in prevalence of patterns with high and average intensity formation of combs, and for the north - with high intensity of formation of combs, for them inherent the presence of combinations of axis three radius of hand; for residents of the western region, consists in the predominance of patterns with high, medium and zero intensity formation of combs, and for the south - with average and zero intensity formation of combs, for them also inherent increased pattern of hypothenar; for the eastern region, consists in the predominance of patterns with medium intensity formation of combs, and for the north - with high and zero intensity formation of combs, for them inherent the presence of combinations of axis three radius of hand; for the eastern region consists in prevalence of patterns with high and medium intensity formation of combs, and for the south - with high and zero intensity formation of combs; for northern region consists in presents of patterns with a higher intensity formation of combs and the presence of intermediate three radius of hands, and for the south - with less high or zero intensity formation of combs.